2016
DOI: 10.1007/s12192-016-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor p8 regulates autophagy during diapause embryo formation in Artemia parthenogenetica

Abstract: Autophagy is an essential homeostatic process by which cytoplasmic components, including macromolecules and organelles, are degraded by lysosome. Increasing evidence suggests that phosphorylated AMP-activated protein kinase (p-AMPK) and target of rapamycin (TOR) play key roles in the regulation of autophagy. However, the regulation of autophagy in quiescent cells remains unclear, despite the fact that autophagy is known to be critical for normal development, regeneration, and degenerative diseases. Here, crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Hsf1 is one transcription factor that can serve as a regulator of the desiccation response, but there are likely other regulators (transcriptional and post-transcriptional) that are involved. It is further possible that transcriptional co-activators like p8 may provide specificity to the transcriptional initiation of diapause and desiccation resistance Lin et al, 2016).…”
Section: Regulation Of Desiccation Resistancementioning
confidence: 99%
“…Hsf1 is one transcription factor that can serve as a regulator of the desiccation response, but there are likely other regulators (transcriptional and post-transcriptional) that are involved. It is further possible that transcriptional co-activators like p8 may provide specificity to the transcriptional initiation of diapause and desiccation resistance Lin et al, 2016).…”
Section: Regulation Of Desiccation Resistancementioning
confidence: 99%
“…Previous studies have identified the core autophagy-related genes (ATGs): ATG8 protein homologs accumulate in starved C. elegans , including dauer larvae and aging adults [ 35 ]. However, in Artemia parthenogenetica , autophagy levels decrease drastically in diapause embryos, and the protein levels of ATG5 and ATG8 are downregulated [ 36 ]. While some researchers proposed that autophagy is upregulated to fulfil the energy requirements for survival by nutrient recycling [ 37 ], others have suggested that, under some conditions, cell cycle arrest is associated with reduced autophagy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the direct evidence for linkage between autophagy and insect diapause is still scarce. However, autophagy has been demonstrated to play roles in the diapause process of other organisms, such as crustacean Artemia parthenogenetica [ 55 ] and harvestmen Amilenus aurantiacus [ 56 ]. Therefore, it is very interesting to consider that autophagy plays a role in insect diapause, which necessitates further verification.…”
Section: Discussionmentioning
confidence: 99%